STRATEGI KOMUNIKASI PENGURUS KNPI SULAWESI SELATAN UNTUK MENDORONG PARTISIPASI PROGRAM KEMITRAAN ORGANISASI KEPEMUDAAN - Anugra Nursamsami; Jasmal A. Syamsu; Muh. Hasrul (Fakultas Dakwah dan Komunikasi, 2020)
Communication provides tools for making decisions, implementing decisions, receiving feedback, and correcting organizational goals and procedures. This study aims to find a picture of the communication strategy at KNPI South Sulawesi as a way of participation of youth and to find out the form of the involvement of youth organizations that gather in KNPI South Sulawesi. This research is a qualitative study that is described descriptively and carried out at KNPI South Sulawesi and several youth organizations that accumulate in the KNPI South Sulawesi in South Sulawesi, South Sulawesi province, Indonesia. Data collection techniques used include observation, interviews, document review (literature study), and documentation. Representation records systemically the events, behaviors, objects seen, and other things that needed in support of the research carried out while the interview done by interviewing the informant, who is the source of information.